2015
DOI: 10.18632/oncotarget.3221
|View full text |Cite
|
Sign up to set email alerts
|

miR-93 Promotes Cell Proliferation in Gliomas through Activation of PI3K/Akt Signaling Pathway

Abstract: The PI3K/Akt signaling pathway is frequently activated in various human cancer types and plays essential roles in development and progression of cancers. Multiple regulators, such as phosphatase and tensin homolog (PTEN) and PH domain leucine rich repeat protein phosphatases (PHLPP), have also found to be involved in suppression of the PI3K/Akt signaling pathway. However, how suppressive effects mediated by these regulators are concomitantly disrupted in cancers, which display constitutively activated PI3K/Akt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
87
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 101 publications
(89 citation statements)
references
References 59 publications
2
87
0
Order By: Relevance
“…Similarly, in breast cancers, miR-93 has been found to decrease multiple carcinogenic processes, interestingly, in an Nrf2-dependent manner [23]. On the other hand, in some malignancies, such as gastric cancer, hepatocellular carcinoma, non-small-cell lung cancer, osteosarcoma, ovarian cancer, and gliomas, miR-93 down-regulates tumour suppressor (mostly PTEN) expression and has consequently been linked to more aggressive cancer phenotypes in both experimental and clinical studies [38-43]. …”
Section: Discussionmentioning
confidence: 99%
“…Similarly, in breast cancers, miR-93 has been found to decrease multiple carcinogenic processes, interestingly, in an Nrf2-dependent manner [23]. On the other hand, in some malignancies, such as gastric cancer, hepatocellular carcinoma, non-small-cell lung cancer, osteosarcoma, ovarian cancer, and gliomas, miR-93 down-regulates tumour suppressor (mostly PTEN) expression and has consequently been linked to more aggressive cancer phenotypes in both experimental and clinical studies [38-43]. …”
Section: Discussionmentioning
confidence: 99%
“…In recent years, miR-93 has been found to be deregulated and to generally have a promoting role in certain human cancer types (23,24).…”
Section: Discussionmentioning
confidence: 99%
“…Although a few studies have shown that miR-93 may functionally interact with PTEN, this has only been reported in cardiomyocyte apoptosis, osteosarcoma, ovarian cancer, glioma, hepatocellular carcinoma and prostate cancer (14)(15)(16)(17)(18)(19)(20). Therefore, it remains to be determined whether miR-93 is also functionally associated with PTEN in breast cancer, and whether such an association contributes to the induction of EMT and drug resistance in breast cancer cells.…”
Section: Introductionmentioning
confidence: 99%